Design and Production of Innovative Turbomachinery Components via Topology Optimization and Additive Manufacturing - Enrico Meli; Andrea Rindi; Alessandro Ridolfi; Rocco Furferi; Francesco Buonamici; Giuseppe Iurisci; Simone Corbò; Francesco Cangioli (International Journal of Rotating Machinery)
The present paper proposes a methodology to design and manufacture optimized turbomachinery components by leveraging the potential of Topology Optimization (TO) and Additive Manufacturing (AM). The method envisages the use of TO to define the best configuration of the rotoric components in terms of both static and dynamic behavior with a resultant reduction of overall weight. Eventually, the topology-optimized component is manufactured by using appropriate materials that can guarantee valid mechanical performances. The proposed strategy has been applied to a 2D impeller used for centrifugal compressors to prove the effectiveness of a TO+AM-based approach. Although this approach has never been extensively used before to centrifugal compressors and expanders, its application on rotor and stator components might unlock several benefits: tuning the natural frequencies, a reduction in the stress level, and a lighter weight of the rotating part. These objectives can be reached alone or in combination, performing a single analysis or a multiple analyses optimization. Finally, the introduction of AM technologies as standard manufacturing resources could bring sensible benefits with respect to the time to production and availability of components. Such aspects are essential in the Oil and Gas context, when dealing with new projects but also for service operations.